Electroacupuncture for lumbar disc herniation: A protocol for systematic review and meta-analysis - Shen, Yuquan (Medicine (Baltimore), 2020)
BACKGROUND: This systematic review aims to evaluate the effectiveness of electroacupuncture in treatment of lumbar disc herniation (LDH). METHODS: Electronic databases of all electroacupuncture for LDH will be searched at PubMed, Cochrane Library, Springer, EMBASE, China National Knowledge Infrastructure (CNKI), Wan-Fang, and Chinese Biological Medical disc, (CBM) from inception to February 29, 2020, with language restricted in Chinese and English. The primary outcome is Japanese Orthopedic Association Scores, a quantification scale for a comprehensive assessment according to patients’ subjects feeling and objective function. Secondary outcomes included visual analogue scale (VAS), Oswestry dysfunction index (ODI), Pittsburgh sleep quality index (PSQI), Self-rating anxiety scale (SAS), self-depression rating scale (SDS), follow-up relapse rate. The systematic review and searches for randomized controlled trials of this therapy for LDH. The Cochrane RevMan V5.3 bias assessment tool is implemented to assess bias risk, data integration risk, meta-analysis risk, and subgroup analysis risk (if conditions are met). Mean difference (MD), standard mean deviation (SMD) and binary data will be used to represent continuous results. RESULTS: This study will provide a comprehensive review and evaluation of the available evidence for the treatment of LDH with this therapy. CONCLUSION: This study will provide new evidence to evaluate the effectiveness and side effects of electroacupuncture for LDH. Due to the data is not personalized, no formal ethical approval is required.